Antibiotic resistance in commensal intestinal microflora - Kmeť, Vladimír; Straková, Eva (Folia microbiologica, 2010)
The susceptibility toward antibiotics was determined by disc and MIC methods in Lactobacillus and, for comparison, in Escherichia coli strains isolated from cloacal swabs of broiler chickens derived from various farms in Slovakia. The occurrence of acquired tetracycline resistance in E. coli and lactobacilli isolated from the same sample was similar. The presence of tet(M), tet(S), tet(L) and ermB genes was demonstrated in lactobacilli while the tet(M) gene was not detected in E. coli.
Keywords: kur domácí; polymerázová řetězová reakce; Slovakia; Slovenská republika; Cloaca; Chickens; Lactobacillus; Drug Resistance, Bacterial; antibakteriální látky; Microbial Sensitivity Tests; kloaka; Escherichia coli; Animals; Genes, Bacterial; Anti-Bacterial Agents; bakteriální léková rezistence; zvířata; mikrobiální testy citlivosti; Financing, Organized; Polymerase Chain Reaction; financování organizované; bakteriální geny